Corporate Governance Reforms and Financial Reporting Improvements (gjstudies, 2019)
This research investigates the relationship between corporate governance reformsand improvements in financial reporting quality, employing a novel methodologicalframework that integrates institutional theory with computational text analysis. Whileprior studies have predominantly focused on quantitative metrics of governance, thispaper introduces a qualitative, longitudinal approach to assess how governance reforms manifest in narrative disclosures and reporting practices over time. We developa unique analytical model that examines the evolution of governance language in annual reports, board committee charters, and audit committee minutes, tracing thediffusion of reform principles into organizational discourse. Our methodology combines content analysis, semantic network mapping, and temporal sequence analysis toidentify patterns of adoption and internalization of governance norms. The study spansa fifteen-year period following major regulatory interventions, allowing for an examination of both immediate compliance effects and longer-term cultural shifts. We find thatgovernance reforms trigger distinct phases of reporting improvement: an initial periodof symbolic compliance characterized by superficial linguistic changes, followed by substantive integration where governance principles become embedded in decision-makingprocesses and reporting routines. The research reveals that the most significant improvements in financial reporting quality occur when governance language shifts frompassive, compliance-oriented discourse to active, principle-based narratives that reflectgenuine board engagement. Furthermore, we identify specific linguistic markers thatdistinguish cosmetic compliance from meaningful reform implementation. These findings contribute to governance theory by demonstrating how regulatory interventionstranslate into organizational practice through discursive mechanisms, offering policymakers and practitioners a more nuanced understanding of reform effectiveness beyondtraditional compliance metrics.